Evidence for the Existence of Secretory Granule (Dense-Core Vesicle)-Based Inositol 1,4,5-Trisphosphate-Dependent Ca(2+) Signaling System in Astrocytes - Hur, Yong Suk (Public Library of Science, 2010)
BACKGROUND: The gliotransmitters released from astrocytes are deemed to play key roles in the glial cell-neuron communication for normal function of the brain. The gliotransmitters, such as glutamate, ATP, D-serine, neuropeptide Y, are stored in vesicles of astrocytes and secreted following the inositol 1,4,5-trisphosphate (IP(3))-induced intracellular Ca(2+) releases. Yet studies on the identity of the IP(3)-dependent intracellular Ca(2+) stores remain virtually unexplored. PRINCIPAL FINDINGS: We have therefore studied the potential existence of the IP(3)-sensitive intracellular Ca(2+) stores in the cytoplasm of astrocytes using human brain tissue samples in contrast to cultured astrocytes that had primarily been used in the past. It was thus found that secretory granule marker proteins chromogranins and secretogranin II localize in the large dense core vesicles of astrocytes, thereby confirming the large dense core vesicles as bona fide secretory granules. Moreover, consistent with the major IP(3)-dependent intracellular Ca(2+) store role of secretory granules in secretory cells, secretory granules of astrocytes also contained all three (types 1, 2, and 3) IP(3)R isoforms. SIGNIFICANCE: Given that the secretory granule marker proteins chromogranins and secretogranin II are high-capacity, low-affinity Ca(2+) storage proteins and chromogranins interact with the IP(3)Rs to activate the IP(3)R/Ca(2+) channels, i.e., increase both the mean open time and the open probability of the channels, these results imply that secretory granules of astrocytes function as the IP(3)-sensitive intracellular Ca(2+) store.